Endogenous ballot structures: The selection of open and closed lists in Colombia's legislative elections. (October 2017) - Achury, Susan; Ramírez, Margarita; Cantú, Francisco
Abstract: What are the incentives for parties to personalize electoral competition? This paper proposes that both open and closed lists give congruity, rather than tension, to the interests of party leaders and candidates. However, the efficacy of each list type depends on the electoral returns expected from promoting the partisan and personal vote. To test this argument, we analyze the choices of parties over the ballot structure by leveraging an unusual institutional feature of the Colombian legislative elections, wherein parties are allowed to present either an open or a closed list, varying their choices across electoral districts and contests. Our empirical analysis shows that parties are more likely to open their lists in high-magnitude districts and wherever they have a strong, local electoral organization. We also find a positive relationship between the selection of closed lists among personalist parties, providing evidence to previous arguments proposing a closed list as a tool to concentrate campaign efforts behind a particular candidate.